2007
DOI: 10.1073/pnas.0704008104
|View full text |Cite
|
Sign up to set email alerts
|

Single phage T4 DNA packaging motors exhibit large force generation, high velocity, and dynamic variability

Abstract: Terminase enzyme complexes, which facilitate ATP-driven DNA packaging in phages and in many eukaryotic viruses, constitute a wide and potentially diverse family of molecular motors about which little dynamic or mechanistic information is available. Here we report optical tweezers measurements of single DNA molecule packaging dynamics in phage T4, a large, tailed Escherichia coli virus that is an important model system in molecular biology. We show that a complex is formed between the empty prohead and the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
224
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 178 publications
(237 citation statements)
references
References 40 publications
13
224
0
Order By: Relevance
“…A previously observed, but unexplained feature in phi29, lambda, and T4 packaging is the occurrence of ∼1-to 10-s pauses in DNA translocation (9,11,12). Pausing increases sharply at high filling (Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…A previously observed, but unexplained feature in phi29, lambda, and T4 packaging is the occurrence of ∼1-to 10-s pauses in DNA translocation (9,11,12). Pausing increases sharply at high filling (Fig.…”
Section: Significancementioning
confidence: 99%
“…DNA packaging in bacteriophages phi29, lambda, and T4 has been directly measured via single-molecule manipulation with optical tweezers and the packaging motors have been shown to generate forces of >60 pN, among the highest known for biomotors, while translocating DNA at rates ranging from ∼100 bp (for phage phi29, which packages a 19.3-kbp genome into a 42 × 54-nm prohead shell) up to as high as ∼2,000 bp/s (for phage T4, which packages a 171-kbp genome into a 120 × 86-nm prohead) (9)(10)(11)(12)(13)(14)(15). The force resisting packaging rises steeply with prohead filling and has been proposed to play an important role in driving viral DNA ejection (16).…”
mentioning
confidence: 99%
“…Our previous optical tweezers assays with WT motor complexes revealed that packaging could be triggered to occur within seconds of bringing a target DNA molecule into contact with a procapsidterminase complex and that packaging at a high speed averaging 580 bp/s usually proceeded within seconds (8). Similar optical tweezers assays were previously applied to measuring packaging dynamics in bacteriophage phi29 and have also recently been applied to bacteriophage T4 (9). These optical tweezers assays also revealed that all of these viral motors were very strong, exerting Ͼ50 pN of force during packaging.…”
mentioning
confidence: 96%
“…Structural studies (12,16,19) and single-molecule optical tweezers (3,13) and fluorescence spectroscopy (20,21) approaches have been used to dissect the mechanochemical steps of DNA translocation. However, the transient nature of DNA and protein interactions at the initiation stage, which involve insertion of the dsDNA end into the prohead and triggering of translocation, has been a major challenge (22).…”
Section: Significancementioning
confidence: 99%
“…The T4 packaging motor, a pentamer of gp17 (70 kDa) (large terminase protein) assembled on the gp20 portal dodecamer (12) is the fastest (packaging rate up to ∼2,000 bp/s) of the viral packaging motors studied (13). Gp17 possesses all of the basic enzymatic activities necessary for generating a DNA-full head: ATPase, nuclease, and translocase (14,15).…”
mentioning
confidence: 99%